The estimated prevalence of exposure to carcinogens, asthmagens, and ototoxic agents among healthcare workers in Australia. Issue 7 (31st March 2020) - Rai, Rajni; Fritschi, Lin; Carey, Renee N.; Lewkowski, Kate; Glass, Deborah C.; Dorji, Nidup; El‐Zaemey, Sonia
Abstract: Background: Healthcare workers are occupationally exposed to various hazardous chemicals and agents that can potentially result in long‐term adverse health effects. These exposures have not been comprehensively examined at a population level. The aim of this study was to examine occupational exposures to a wide range of asthmagens, carcinogens, and ototoxic agents among healthcare workers in Australia. Methods: Data were collected as part of the Australian Work Exposures Studies, which were computer‐assisted telephone surveys conducted in 2011, 2014, and 2016 to assess the prevalence of occupational exposures to carcinogens, asthmagens, and ototoxic agents, respectively, among Australian workers. Using data on healthcare workers, the prevalence of exposures to these agents was calculated and associations of demographic variables and occupation groups with exposure status were examined. Results: The prevalence of exposure to at least one asthmagen, carcinogen, and ototoxic agent was 92.3%, 50.7%, and 44.6%, respectively. The most common exposures were to (a) cleaning and sterilizing agents in the asthmagen group; (b) shift work in the carcinogen group; and (c) toluene and p‐xylene among ototoxic agents. Exposure varied by occupation, with exposure to carcinogens and ototoxic agents highest among personal carers and exposure to carcinogens most likely among nursing professionals and health and welfare support workers. Conclusion: The results demonstrate that a substantial proportion of Australian healthcare workers are occupationally exposed to asthmagens, carcinogens, and ototoxic agents. These exposures are more common among certain occupational groups. The information provided by this study will be useful in prioritizing and implementing control strategies.